KEBIJAKAN MERDEKA BELAJAR DI PENDIDIKAN DASAR: ANALISIS IMPLEMENTASI DAN HASIL - SUPARMAN, SUPARMAN; MUHAMMAD, MUHAMMAD (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
The aim of this research is to examine 1). The concept of Independent Learning is taken from the opinions of experts taken from relevant references, 2). The Independent Learning Policy launched by the government through the Ministry of Education and Culture, 3). Implementation of the Independent Learning Curriculum as a step in implementing it in Elementary Schools, 4). Independent Learning Curriculum Structure in Elementary Schools. This research also explains the development of the implementation of the Merdeka Mandiri Curriculum in Elementary Schools. The Government through the Ministry of Education, Research and Technology provides implementation options including: Implementation of the Merdeka Mandiri Learning Curriculum, Implementation of the Merdeka Mandiri Curriculum to Change and Implementation of the Mandiri Sharing Curriculum. The method used in writing this article is to use literature study using various types of scientific article sources from various journals to look for theories and supporting data. ABSTRAKTujuan dari penelitian ini adalah mengkaji 1). Konsep Merdeka Belajar yang diambil dari pendapat para ahli yang diambil dari referensi yang relevan , 2). Kebijakan Merdeka Belajar yang dicanangkan oleh pemerintah melalui Kemendikbudristek, 3). Implementasi Kurikulum Merdeka Belajar sebagai langkah penerapan di Sekolah Dasar, 4). Struktur Kurikulum Merdeka Belajar di Sekolah Dasar. Dalam penelitian ini juga dijelaskan pengembangan Implementasi Kurikulum Merdeka Mandiri di Sekolah Dasar, Pemerintah melalui Kementerian Pendidikan Riset dan Tekhnologi memberikan pilihan pengimplementasian antara lain: Implementasi Kurikulum Merdeka Mandiri Belajar, Implementasi Kurikulum Merdeka Mandiri Berubah dan Implementasi Kurikulum Mandiri Berbagi. Metode yang digunakan dalam penulisan artikel ini adalah menggunakan studi literatur dengan menggunakan berbagai jenis sumber artikel ilmiah dari berbagai jurnal untuk mencari teori serta data yang mendukung.